Training of trainers: An action-based research for improving the pedagogical skills of academicians - Bayram Özer; Volkan Duran; Mustafa Tekke (International Journal of Evaluation and Research in Education (IJERE), 2020)
Based on the philosophy of lifelong education, private/public institutions and organizations invest in continuous training of human resources. Universities also organize in-service trainings regarding the general principles of teaching and learning in the context lifelong learning activities for the development of the pedagogical skills of the academicians who have difficulty in using teaching skills and principles in the courses in their universities. Therefore, a Project entitled as Training of Trainers based on action research based on qualitative research design was carried out for aiming at providing pedagogical education for the academicians who work in different departments of Ondokuz Mayis University who are experts in different disciplines but who do not have pedagogical background in order to gain experience in basic skills and principles in education area so as to improve the quality of education in this way. During the project, which lasted for a total of 2 years, 246 academicians were trained in 24 different subjects, the opinions of the participants were taken and the distribution of these views was reflected in the tables in text. Finally, the asymptotic Significance (2-sided) for Pearson Chi-Square indicates of the yes/no answer indicates that there is a dramatic change regarding the effectiveness of the program. It is seen that it meets the needs of academicians. Therefore, the program based on action research design shows that such in-service pedagogical programs could be useful for higher education in this respect.